JESZCZE O „SZKOLE” NIKOŁAJA KOLADY. W STRONĘ POSZUKIWAŃ FORMALNYCH - Piłat, Walenty (Przegląd Rusycystyczny, 2016)
Еще про "школу" Николая Коляды. В сторону формвльных исканий В статье подвергаются анализу пьесы драматургов из екатеринбурга. особое внимание обращено на драмы олега Богаева, василия сигарева, Андрея Архипова и других. Подчеркивается связь авторов «школы» с некоторыми элементами поэтики Николая Коляды. ONE MORE THING ABOUT NIKOLAI KOLYADA’S “SCHOOL”. TOWARDS FORMAL RESEARCH This article analyzes a selection of works by authors belonging to so-called Nikolai Kolyada’s “school:” oleg Bogayev, Vasilii Sigarev, Yaroslava Pullinovich, Vladimir Zuyev and others. The main attention is given to the problem of the characters’ insecurity in the existing world, as well as to the artistic presentation of various social consequences of war.